2014
DOI: 10.1371/journal.pone.0090754
|View full text |Cite
|
Sign up to set email alerts
|

CD4 Counts and Viral Loads of Newly Diagnosed HIV-Infected Individuals: Implications for Treatment as Prevention

Abstract: ObjectiveTo report the viral load and CD4 count in HIV-infected, antiretroviral naïve, first -time HIV-testers, not immediately eligible for treatment initiation by current South Africa treatment guidelines.DesignThis was a cross-sectional study in a high-volume, free-of-charge HIV testing centre in Soweto, South Africa.MethodsWe enrolled first time HIV testers and collected demographic and risk-behaviour data and measured CD4 count and viral load.ResultsBetween March and October 2011, a total of 4793 adults a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
13
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 16 publications
(18 reference statements)
4
13
1
Order By: Relevance
“…Gender differences in our study were consistent with several sources reporting on HCT (Govender et al, 2014;Govindassamy et al, 2013;May et al, 2010;Patten et al, 2013); most individuals referred to the call center were female (similar to Govindassamy et al, 2013), whom were more likely to link to care than males and had higher CD4 counts. Govindassamy et al (2013) reported a similar mean CD4 count (481) among women.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Gender differences in our study were consistent with several sources reporting on HCT (Govender et al, 2014;Govindassamy et al, 2013;May et al, 2010;Patten et al, 2013); most individuals referred to the call center were female (similar to Govindassamy et al, 2013), whom were more likely to link to care than males and had higher CD4 counts. Govindassamy et al (2013) reported a similar mean CD4 count (481) among women.…”
Section: Discussionsupporting
confidence: 90%
“…AIDS Care 923 have procured CD4 counts that were comparably high. Mugglin et al's (2012) meta-analysis found that among six studies median CD4 counts ranged between 154 and 274, and Govender et al (2014) found a median CD4 count of 364, both slightly lower than our median count of 370.…”
Section: Discussioncontrasting
confidence: 61%
“…Yield of HIV positive individuals (HIV positivity) was reported in 29 home studies 14,15,18,27,2932,34,36,38,41–45,63,65,66,68,7073,88,89 , one home with self-testing 11 , 12 mobile 10,13,68,72,9295,97,98,103,107,114 , five campaign 46,47,76,77,120 , three workplace 79,80,121 , four key population 12,115,116,122 , four index partner 4850,88 , 27 facility VCT 5456,64,81,84,88,9193,95,98,102,104107,114,118120,123127 , and 17 facility PITC 56,57,59,60,81,8388,99,110113,126 studies. Community-based strategies for the general population had lower HIV positivity (6–11%) than facility HTC (18–20%), whereas targeted community HTC for key populations and sexual partners of index patients had the highest HIV yield (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The proportion of individuals with CD4 count of less than 350 cells μL −1 at HIV diagnosis was reported in 7 home 14,38,42,43,65,72,73 , 3 mobile 91,94,114 , 3 campaign 46,47,76 , 8 facility VCT 60,81,107,126,127,129131 and 5 facility PITC studies 61,81,99,126,130 . Community-based strategies identified HIV-positive individuals at higher CD4 counts than facility HTC, with campaign having the lowest proportion with CD4 count less than 350 cells μL −1 (26%, 95% CI = 22–30%) (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The different transition probabilities associated with different CD4 counts are primarily intended to distinguish the behaviour of people with <200 CD4 cells/lL (AIDS-stage infection) and also capture differences in mortality rates. We assume that people with AIDS-stage infection have a symptomatic testing rate above the standard testing rate for their population cohort, which gives us an estimated median CD4 count at diagnosis of 340 cells/lL in 2015, approximately on par with other studies [21,22]. We assume that treatment spots are first taken by those with lower CD4 counts, which give us a mean CD4 count at time of treatment initiation of 190 cells/ll, again comparable to other studies [21].…”
Section: Model Transitionsmentioning
confidence: 99%